Where They Live : District-Level Measures of Poverty, Average Consumption, and the Middle Class in Central Asia - Seitz, William (World Bank, Washington, DC, 2019)
Rapid economic growth over the past two decades lifted millions of people out of poverty in Central Asia. But the uneven spread of prosperity left many communities struggling to catch up. To support lagging regions within countries, each of the region's five national governments has made convergence a pillar of their development strategies. An imperfect patchwork of household surveys allows policy makers to monitor progress and identify some spatial disparities. But these share an important weakness: none of the official surveys in the region is representative when disaggregated to the level of districts. Islands of poverty and prosperity are thus lost in the averages -- leading to targeting inaccuracies that can slow the pace of poverty reduction. This study partially addresses the challenge. The accuracy of key welfare indicators is sharpened well beyond what could be achieved for any country alone by: i) unifying survey data from across the region and ii) applying the techniques of small-area estimation. The results provide detailed measures of welfare that in turn can be disaggregated for each district in Central Asia. Comprehensive maps of where the poor and the middle class live are presented, for the entire region and individually for each country.